Suggested Rational Considerations for ANA-IF and ENA-Profile Test Requisition: Clinical Manifestation, Gender, Pattern, and Titer of ANA-IF - Yenny Surjawan; Umi Solekhah Intansari (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: The anti-nuclear antibody immunofluorescence (ANA-IF) test is used for screening of autoantibody presence in patients with suspected autoimmune disease. Positive ANA-IF should be followed-up with extractable nuclear antigens profile (ENA-profile). High ANA-IF sensitivity combined with low ENA-profile sensitivity, and the evolution of ANA-IF requests may result in a higher number of positive ANA-IF but negative ENA-profile. It is necessary to make an objective assessment in determining the conditions in which rational ANA-IF and ENA-profile should be suggested.METHODS: Data were retrieved retrospectively from the medical records of subjects who performed both ANA-IF and ENA-profile. ANA-IF were examined using immunofluorescence principle with cut-off 1:100. ENA-profile which contained sixteen purified antigens was performed using line-immunoblot principle. Data was analyzed descriptively and analytically using SPSS, and significant result was indicated if p<0.05.RESULTS: The ANA-IF result was dominated by negative (44.9%) and positive-speckled, titer 1:100 (32.9%). Of 923 subjects with positive ANA-IF, 45.4% had a negative ENA-profile. Of 751 subjects with negative ANA-IF, 10.2% had positive ENA-profile. In subjects whose specific clinical entity, the ANA-IF sensitivity and negative predictive value (NPV) in detecting ENA-profile were 93.8% and 93.3%, respectively, but the positive predictive value (PPV) was 63.2%. Women with specific autoimmune manifestation accompanied by ANA-IF homogeneous ≥1:100, or centromeres ≥1:100, or speckled ≥1:320 might have been predicted as subsequent positive ENA-profile with area under curve (AUC) of 77.2%, 76.9%, 79.2%, respectively.CONCLUSION: ANA-IF should only be indicated for those with specific clinical symptoms. For woman with typical symptoms, the presence of positive ANA-IF with homogeneous ≥1:100, or centromeres ≥1:100, or speckled ≥1:320 should be further followed-up by ENA-profile.KEYWORDS: ANA-IF, ENA-profile, autoimmune, autoantibody